Effect of Pregnancy towards Prognosisof Women and Babies with COVID-19 - Sinaga, Luhut Parsaulian (Indonesian Journal of Obstetrics & Gynecology Science, 2023)
Objective: Analyzing the relationship of pregnancy with COVID-19 towards the prognostic profiles in mothers and babies.Method: Observational analytics with cross sectional study approach. Data collection through medical records of pregnant women infected with COVID-19 who were treated at Kebayoran Lama Hospital from October 2020 to September 2021.Results: Chi-square statistical test between among women with COVID-19 on prognostic profiles obtained probability value p-value = 0.001 (p-value < 0.05) and Chi-square statistical test among pregnant women with COVID-19 on prognostic profiles in infants obtained a probability value of 0.0001 (p-value < 0.05).Conclusion: Aspects of severity and duration of treatment in cases of pregnancy with COVID-19 are positively related to the prognostic profiles in pregnant women at Kebayoran Lama Hospital. Aspects of COVID-19 exposure in infants, length of treatment, and complication status in cases of pregnancy with COVID-19 are positively related to the prognostic profiles in infants at Kebayoran Lama Hospital.Pengaruh Kehamilan terhadap PrognosisWanita dan Bayi dengan Covid-19AbstrakTujuan: Menganalisis hubungan kehamilan dengan COVID-19 terhadap profil prognosis pada ibu dan bayi.Metode: Analitik observasional dengan pendekatan studi potong lintang. Pengambilan data melalui rekam medis ibu hamil yang terinfeksi COVID-19 yang dirawat di Rumah Sakit Kebayoran Lama sejak Oktober 2020 sampai dengan September 2021.Hasil: Uji statistik Chi-square antara ibu hamil dengan COVID-19 terhadap profil prognosis mendapatkan nilai probabilitas p-value = 0,001 (nilai p < 0,05) dan uji statistik Chi-square antara ibu hamil dengan COVID-19 terhadap profil prognosis pada bayi didapatkan nilai probabilitas sebesar 0,0001 (p value < 0,05).Kesimpulan: Aspek derajat keparahan dan lama perawatan dalam kasus kehamilan dengan COVID-19 berhubungan positif terhadap profil prognosis pada ibu hamil di Rumah Sakit Kebayoran Lama. Aspek paparan COVID-19 pada bayi, lama perawatan, dan status komplikasi pada kasus kehamilan dengan COVID-19 berhubungan positif terhadap profil prognosis pada bayi di Rumah Sakit Kebayoran Lama.Kata kunci: kehamilan, COVID-19, prognosis, ibu, bayi